2017
DOI: 10.1093/ndt/gfw415
|View full text |Cite
|
Sign up to set email alerts
|

The link between phenotype and fatty acid metabolism in advanced chronic kidney disease

Abstract: Advanced CKD in rats with adenine-induced chronic interstitial nephropathy results in profound changes in the serum metabolome, activation of inflammatory, oxidative and fibrotic pathways, and suppression of cytoprotective and antioxidant pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 47 publications
2
57
0
1
Order By: Relevance
“…The total protein concentration was determined using Pierce™ BCA Protein Assay Kit (23227, Thermo Scientific, USA) according to the manufacturer's instructions. Protein expression was performed by Western blot analyses as described previously [17], [18]. The ratio of each protein was calculated by densitometry using free ImageJ software (version 1.48 v, NIH, Bethesda, MD, USA) and Band densities were normalized by Histone H3 or GAPDH expression levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total protein concentration was determined using Pierce™ BCA Protein Assay Kit (23227, Thermo Scientific, USA) according to the manufacturer's instructions. Protein expression was performed by Western blot analyses as described previously [17], [18]. The ratio of each protein was calculated by densitometry using free ImageJ software (version 1.48 v, NIH, Bethesda, MD, USA) and Band densities were normalized by Histone H3 or GAPDH expression levels.…”
Section: Methodsmentioning
confidence: 99%
“…Despite being relatively silent in normal adult kidneys, Wnt/β-catenin signaling is activated in the different CKD, such as obstructive nephropathy, adriamycin nephropathy, chronic allograft nephropathy and diabetic nephropathy [13], [14], [15], [16], which was accompanied by oxidative stress and inflammation. It was reported that activated oxidative stress and inflammation were closed associated with dysregulation of amino acid, uremic toxin (indoxyl sulfate, uric acid), bile acid, fatty acid, triglyceride, glycerophospholipid metabolisms in rats with chronic kidney disease [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrosis is a wound-healing response to either acute or chronic cellular injury that is characterized by the accumulation of extracellular matrix (ECM). Excessive evidence demonstrated that fibrogenesis is associated with renin-angiotensin system, inflammation and oxidative stress, transforming growth factor β (TGF-β)/Smad signaling, Wnt/βcatenin signaling and lipid metabolism [1][2][3][4][5][6][7][8][9][10]. Among them, TGF-β/ Smad signaling plays an important role in fibrosis [1,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Renal fibrosis is closely associated with mounting mediators and signaling pathways, such as oxidative stress, inflammation, microRNAs, transforming growth factor β1 (TGF-β1)/Smad and Wnt/β-catenin (Fig. 2), as well as the dysregulated uremic toxins, amino acids and lipid metabolism [92][93][94][95][96][97][98][99][100]. In recent decades, natural small molecules have gradually become an important therapeutic strategy for the prevention and treatment of renal fibrosis worldwide [22,101,102].…”
Section: Renal Disease and Fibrosismentioning
confidence: 99%